T&T Clark companion to the Septuagint - Aitken, J. K. (Bloomsbury companions, 2015)
"The Septuagint is the Greek translation of the Hebrew Bible and the scriptures read by early Christians. Septuagint studies have been a growth field in the past twenty years. It has become an area of interest not only for textual criticism of the Hebrew Bible but as a product of Judaism in the Graeco-Roman world. It is even being utilized occasionally by scholars of Greek religion. At the same time renewed interest in the daughter versions (Syriac, Vulgate, Ethiopic, Coptic etc.) has thrown new attention onto the Septuagint. This Companion provides a cutting-edge survey of scholarly opinion on the Septuagint text of each biblical book. It covers the characteristics of each Septuagint book, its translation features, origins, text-critical problems and history. As such it provides a comprehensive companion to the Septuagint, featuring contributions from experts in the field."--